2021
DOI: 10.2196/22723
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Detected Ambient Speech and Self-Reported Measures of Anxiety and Depression: Exploratory Observational Study

Abstract: Background The ability to objectively measure the severity of depression and anxiety disorders in a passive manner could have a profound impact on the way in which these disorders are diagnosed, assessed, and treated. Existing studies have demonstrated links between both depression and anxiety and the linguistic properties of words that people use to communicate. Smartphones offer the ability to passively and continuously detect spoken words to monitor and analyze the linguistic properties of speec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
2
17
0
1
Order By: Relevance
“…We use LIWC to count the percentage of all words collected from the person that fall within LIWC's death category and refer to this as the death-related words feature. In our previous work, we showed that the incidence of death-related words has been shown to have an association with symptoms of SAD, GAD, and depression [35]. The previous work of Di Matteo et al [35] also contains further methodological and implementation details of this LIWC-based feature extraction.…”
Section: Death-related Wordsmentioning
confidence: 93%
See 1 more Smart Citation
“…We use LIWC to count the percentage of all words collected from the person that fall within LIWC's death category and refer to this as the death-related words feature. In our previous work, we showed that the incidence of death-related words has been shown to have an association with symptoms of SAD, GAD, and depression [35]. The previous work of Di Matteo et al [35] also contains further methodological and implementation details of this LIWC-based feature extraction.…”
Section: Death-related Wordsmentioning
confidence: 93%
“…In our previous work, we showed that the incidence of death-related words has been shown to have an association with symptoms of SAD, GAD, and depression [35]. The previous work of Di Matteo et al [35] also contains further methodological and implementation details of this LIWC-based feature extraction.…”
Section: Death-related Wordsmentioning
confidence: 93%
“…Di Matteo et al [ 23 ] explored the relationship between linguistic features of speech and anxiety. Their work used passively collected intermittent samples of audio data from participants’ smartphones, collected over a 2-week period, as input.…”
Section: Introductionmentioning
confidence: 99%
“…Studies used a range of technologies to collect active/subjective, passive/objective, and mixed (i.e., active/subjective and passive/objective) data. Studies employing passively/objectively collected data often produced predictive models with high accuracy in the detection of depression severity involving significant predictors such as geospatial movement, sleep duration, delayed sleep phase, circadian rhythm, audio features, language, accelerometer oscillation, and light exposure during bedtime [ 12 , 29 , 49 , 50 , 52 , 56 ]. Considering the type of technology, reviewed studies employed mobile technology (handheld IT devices such as smartphones, palmtops, tablets, laptops, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessing mood include [ 1 , 2 , 6 , 8 , 12 , 15 , 18 , 21 , 24 , 27 , 29 , 30 , 31 , 33 , 35 , 37 , 40 , 45 , 46 , 50 , 51 , 66 , 67 , 71 , 72 . 73 , 77 , 79 , 80 , 82 , 86 , 87 , 88 , 89 , 94 , 100 , 102 , 103 , 104 , 105 , 109 , 114 , 121 , 122 , 125 , 130 , 131 , 135 , 136 , 138 , 139 , 141 , 142 , 144 , 147 , 148 , 150 , 151 , 172 , 173 , 174 , 181 , 183 , 186 , 188 , 190 , 191 , 192 , 193 , 194 …”
unclassified